The feedback effects of aerosols from different sources on the urban boundary layer in Beijing China. (15th May 2023) - Xin, Jinyuan; Ma, Yongjing; Zhao, Dandan; Gong, Chongshui; Ren, Xinbing; Tang, Guiqian; Xia, Xiangao; Wang, Zifa; Cao, Junji; de Arellano, Jordi Vilà-Guerau; Martin, Scot T.
Abstract: The interaction of aerosols and the planetary boundary layer (PBL) plays an important role in deteriorating urban air quality. Aerosols from different sources may have different effects on regulating PBL structures owing to their distinctive dominant compositions and vertical distributions. To characterize the complex feedback of aerosols on PBL over the Beijing megacity, multiple approaches, including in situ observations in the autumn and winter of 2016–2019, backward trajectory clusters, and large-eddy simulations, were adopted. The results revealed notable distinctions in aerosol properties, vertical distributions and thermal stratifications among three types of air masses from the West Siberian Plain (Type-1), Central Siberian Plateau (Type-2) and Mongolian Plateau (Type-3). Low loadings of 0.28 ± 0.26 and 0.15 ± 0.08 of aerosol optical depth (AOD) appeared in the Type-1 and Type-2, accompanied by cool and less stable stratification, with a large part (80%) of aerosols concentrated below 1500 m. For Type-3, the AOD and single scattering albedo (SSA) were as high as 0.75 ± 0.54 and 0.91 ± 0.05, demonstrating severe pollution levels of abundant scattering aerosols. Eighty percent of the aerosols were constrained within a lower height of 1150 m owing to the warmer and more stable environment. Large-eddy simulations revealed that aerosols consistently suppressed the daytime convective boundary layer regardless of their origins, with the PBL height (PBLH) decreasing from 1120 m (Type-1), 1160 m (Type-2) and 820 m (Type-3) in the ideal clean scenarios to 980 m, 1100 m and 600 m, respectively, under polluted conditions. Therefore, the promotion of absorbing aerosols below the residual layer on PBL could be greatly hindered by the suppression effects generated by both absorbing aerosols in the upper temperature inversion layer and scattering aerosols. Moreover, the results indicated the possible complexities of aerosol-PBL interactions under future emission-reduction scenarios and in other urban regions. Graphical abstract: Image 1 Highlights: Aerosol profiles in Siberian air masses are similar but distributed at higher height. PBL in Mongolian-plateau air mass is warmer and stabler than these from Siberia. Aerosols consistently suppress the daytime PBL regardless of their origins. Promotion of inner-PBL absorption aerosols on PBL is hindered by suppression effect.